Intercellular adhesion molecule-1 is a surrogate biomarker for subclinical atherosclerosis in Type 2 diabetes mellitus - Sasikala, Thallapaneni; M Manohar, Suchitra; RR Bitla, Aparna; Sarala, S; Vaikkakara, Suresh (Biomarkers in medicine, 2021)
We aimed to investigate biomarkers of inflammation, oxidative stress as surrogate markers of subclinical atherosclerosis in patients with Type 2 diabetes mellitus (T2DM). Subjects were grouped based on carotid intima media thickness (CIMT). Group 1: healthy controls (CIMT <0.57 mm); Group 2: T2DM without subclinical atherosclerosis (CIMT <0.57 mm); Group 3: T2DM with subclinical atherosclerosis (CIMT ≥0.57 mm). Significantly higher MDA, Hs-CRP, Ox-LDL, PTX-3, IL-6, ICAM-1 and lower FRAP, IL-10 levels in T2DM groups compared with controls (p = 0.001). Changes were more significant in Group 3 compared with Group 2. ICAM-1 had the highest sensitivity and specificity at a cut-off value of >40.34 ng/ml compared with Ox-LDL and PTX-3 (p < 0.001). ICAM can be considered as an alternate surrogate biomarker of CIMT.